The Impact of Rhythmic Distortions in Speech on Personality Assessment - Volín, Jan; Poesová, Kristýna; Skarnitzl, Radek (Research in Language, 2014)
The perennial question as to how perceived otherness in speech projects into listener assessment of one’s personality has been systematically investigated within the field of foreign accentedness, vocal communication of affective states and vocal stereotyping. In the present study, we aimed at exploring non-native listeners’ capacity to respond to differences in natural and modified native speech, particularly whether the manipulation of temporal structure in both stressed and unstressed syllables gives rise to any changes in the perception of the speaker’s personality. The respondents’ intuitive judgements were captured in the domain of the ‘nervousness category’ taken from the five-factor model of personality. Our results indicate an effect of temporal modifications on the listeners’ judgements. Analysis of variance for repeated measures confirmed a highly significant shift of personality evaluations towards the undesired traits (e.g., nervousness, anxiety, querulousness). Several interesting interactions with the semantic contents of the utterances and with the intrinsic qualities of the speakers’ voices were also found. We argue that the effects of accented speech go beyond conscious willingness to accept “otherness” and suggest a method for studying them.